Wpływ działalności klubów bibliotecznych na wzrost zainteresowania ofertą Pedagogicznej Biblioteki Wojewódzkiej w Krakowie na przykładzie Bibliotecznego Klubu Gracza „Zgrane Pionki” .......... 163 - Kruk-Gruca, Anna; Maśko, Sylwia (Skąd się biorą czytelnicy?, 2025)
THE ROLE OF LIBRARY CLUBS IN INCREASING THE INTEREST IN THE OFFER OF THE PROVINCIAL PEDAGOGICAL LIBRARY IN KRAKÓW ON THE EXAMPLE OF A GAMER CLUB ‘ZGRANE PIONKI’The authors present the activities of the library club ‘Zgrane Pionki’ (Checkers in Sync) for board gamers who operate within the Hugo Kołłątaj Provincial Pedagogical Library in Kraków. They discuss the plans, initiatives concerning board games, their implementation, and the effects resulting in the increase of the interest in the offer of the library. They describe activities that promote the institution in the context of forming its public image.